2019
DOI: 10.1371/journal.pone.0218723
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of prior diets, dietary transition and pregnancy on adipose gene expression in dairy heifers

Abstract: Adipose tissue is highly involved in whole-body metabolism and is the main site for lipid synthesis, storage and mobilization in ruminants. Therefore, knowledge about adipose tissue responses to different diets is important, especially in growing heifers as the feeding regimes of replacement heifers affect their future success as dairy cows. However, at gene expression level such knowledge is limited. As part of a larger feed trial, adipose tissue biopsies from 24 Norwegian Red heifers were collected at 12 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Expression of transcripts of ENSBTAG00000031205 (fold-change = 31.5; FDR P = 2.5 x 10 -5 ) that encode 40S ribosomal protein S4 were likewise affected by the breed by diet interaction. Waerp et al (2019) previously observed transcripts of this gene to be differentially abundant in adipose tissue from dairy heifers at 12 months of age versus when they were seven months pregnant when the heifers were fed a high energy diet but not when a lower energy diet was fed. The ENSBTAG00000049315 (foldchange = -178.5; FDR P = 6.6 x 10 -3 ) was the final transcript affected by the breed by diet interaction.…”
Section: Resultsmentioning
confidence: 93%
“…Expression of transcripts of ENSBTAG00000031205 (fold-change = 31.5; FDR P = 2.5 x 10 -5 ) that encode 40S ribosomal protein S4 were likewise affected by the breed by diet interaction. Waerp et al (2019) previously observed transcripts of this gene to be differentially abundant in adipose tissue from dairy heifers at 12 months of age versus when they were seven months pregnant when the heifers were fed a high energy diet but not when a lower energy diet was fed. The ENSBTAG00000049315 (foldchange = -178.5; FDR P = 6.6 x 10 -3 ) was the final transcript affected by the breed by diet interaction.…”
Section: Resultsmentioning
confidence: 93%
“…For Mongolian cattle, ALDOA was the highest expressed gene with 12,960 FPKM in chorid plexus tissue in the brain. ALDOA is primarily related to glycolytic and energy metabolism ( Wærp et al, 2019 ). TNNT2 identified in Yanbian was highly expressed in heart tissue with 5006 FPKM.…”
Section: Resultsmentioning
confidence: 99%
“…According to https://bgee.org/?page=gene&gene_id=ENSBTAG00000007075 , this gene was described as a major histocompatibility complex, class I, A-like precursor and has paralogs to BOLA-A and JSP.1 genes. And has an association with feeding efficiency in Norwegian Red heifers where it is upregulated during diet changes from low-protein-high-energy to low-protein-low-energy feed ( Wærp et al, 2019 ). Yet, for GO classification, we considered only genes with official ID names overlooking functions of genes with prefix ENBST names.…”
Section: Discussionmentioning
confidence: 99%